SEMA3A and IGSF10 Are Novel Contributors to Combined Pituitary Hormone Deficiency (CPHD) - Budny, Bartlomiej; Zemojtel, Tomasz; Kaluzna, Malgorzata; Gut, Pawel; Niedziela, Marek; Obara-Moszynska, Monika; Rabska-Pietrzak, Barbara; Karmelita-Katulska, Katarzyna; Stajgis, Marek; Ambroziak, Urszula; Bednarczuk, Tomasz; Wrotkowska, Elzbieta; et al. (Frontiers in Endocrinology, 2020)
Background: The mutation frequencies of pituitary transcription factors genes in patients with combined pituitary hormone deficiencies (CPHD) vary substantially between populations. However, apart from PROP1 the mutation rate of other genes is low and for almost half of the patients with CPHD the routine sequencing of known genes is unsuccessful in the identification of genetic causes. Methods: A cohort of 66 sporadic and 9 familial CPHD cases (80 patients in total) were subjected to initial testing of the genes PROP1, POU1F1, LHX3, LHX4 and HESX1 using a targeted gene panel and MLPA. In patients who tested negative, a whole exome sequencing approach was employed. Results: In 9 of the familial cases and 32 of the sporadic patient mutations in the PROP1 gene were found (the common pathogenic variants included c.301_302delAG and c.150delA). Mutations were also found in genes so far not related directly to CPHD. A unique homozygous and clinically relevant variant was identified in the SEMA3A gene, which contributes to neural development and his phenotypic spectrum including short stature and isolated hypogonadotropic hypogonadism (IHH). Another pathogenic variant p.A1672T was found in the IGSF10 gene reported to be responsible for delayed puberty and neuronal migration during embryogenesis. Several suspected novel but predicted benign variants were also identified for the CHD7, WDR11 and FGF17 genes. Conclusion: Although the PROP1 defects account for a majority of CPHD patients, identification of rare, less frequent variants constitute a big challenge. Multiple genetic factors responsible for CPHD are still awaiting discovery and therefore the usage of efficient genomic tools (i.e. whole exome sequencing) will further broaden our knowledge regarding pituitary development and function.